The potential of linguistic in the study of aspect and tense in Ancient Greek, with particular attention to New Testament Greek - Nylund, Jan (Lund University, 2024)
This enquiry discusses the potential of a large number of linguistic theories, approaches, concepts etc. from Plato to usage-based linguistics for the understanding of the tense system in Ancient Greek, and particularly in the Greek of the New Testament. It is argued that many significant insights within linguistics in the period from the earliest beginning of linguistic thought up to Saussure have not been noted or included in the discussion of the tenses in New Testament Greek. Many of these insights find corroboration in later linguistic theories in the 20th and 21st centuries. In this volume it is demonstrated that ideas from structuralism and generative linguistics that so far have dominated the debate on the New Testament Greek tense system, such as in the works of Stanley E. Porter, Buist M. Fanning and Constantine R. Campbell, need to be revised or discarded. It is noted that insights from Systemic Functional Linguistics, though favoured by many contributors to the New Testament verbal aspect debate, have been underused. Throughout this volume it is argued that certain theories, both ones preceding and following structuralism and generative linguistics, such as genuine functionalism, grammaticalisation theory, cognitive linguistics and usage-based linguistics, have considerable explanatory power in regard to the understanding and analysis of the New Testament Greek tense system